FAKTOR-FAKTOR YANG MEMPENGARUHI DISMENOREA PADA SISWI DI SMP IT BADRUL ISLAM PEKANBARU TAHUN 2018 - Sari, Adhistie Indah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Adolescence is a dynamic phase of development in an individual's life, which is a period of transition from childhood to adulthood. One of the maturity of young women is characterized by menstruation. And nearly every menstruating woman experiences dysmenorrhoea or menstrual pain. From the initial survey conducted by interviewing students at SMP IT Badrul Islam Pekanbaru, there were still students who did not know about the factors that influence dysmenorrhoea, therefore the authors were interested in conducting research at the junior high school. The research method used is descriptive, data collection used is primary data obtained from respondents and secondary data from the teacher. and presented in the frequency distribution table. The population in this study were students of SMP IT Badrul Islam Pekanbaru and sampling with a total sampling of 30 people. From the results of the study found the majority of knowledgeable respondents Based on the knowledge factor of Badrul Islam Junior High School students had good knowledge of 20 people (67%), doing sports activities and habits x3x a week by 57% with the majority of respondents choosing jogging by 23% and having a pattern and regular eating habits that is 3x a day by 67% (20 people), namely with breakfast breakfast, lunch is rice, side dishes and vegetables and dinner is rice and side dishes. It can be concluded that adequate knowledge of exercise habits and irregular eating patterns can affect dysmenorrhoea. Suggestions for Badrul Islam IT Middle School students to be able to know more information about the factors that influence dysmenorrhoea and how to overcome the dysmenorrhoea from parents, teachers, peers and internet media.